Kinetics and Mechanism Study of Competitive Inhibition of Jack-Bean Urease by Baicalin. (1st October 2013) - Tan, Lirong; Su, Jiyan; Wu, Dianwei; Yu, Xiaodan; Su, Zuqing; He, Jingjin; Wu, Xiaoli; Kong, Songzhi; Lai, Xiaoping; Lin, Ji; Su, Ziren
Abstract : Baicalin (BA) is the principal component of Radix Scutellariae responsible for its pharmacological activity. In this study, kinetics and mechanism of inhibition by BA against jack-bean urease were investigated for its therapeutic potential. It was revealed that the IC50 of BA against jack-bean urease was 2.74 ± 0.51 mM, which was proved to be a competitive and concentration-dependent inhibition with slow-binding progress curves. The rapid formation of initial BA-urease complex with an inhibition constant of K i = 3.89 × 10 − 3 mM was followed by a slow isomerization into the final complex with an overall inhibition constant of K i * = 1.47 × 10 - 4 mM. High effectiveness of thiol protectors against BA inhibition indicated that the strategic role of the active-site sulfhydryl group of the urease was involved in the blocking process. Moreover, the inhibition of BA was proved to be reversible due to the fact that urease could be reactivated by dithiothreitol but not reactant dilution. Molecular docking assay suggested that BA made contacts with the important activating sulfhydryl group Cys-592 residues and restricted the mobility of the active-site flap. Taken together, it could be deduced that BA was a competitive inhibitor targeting thiol groups of urease in a slow-binding manner both reversibly and concentration-dependently, serving as a promising urease inhibitor for treatments on urease-related diseases.